An open banking platform for Germany: A future-oriented alternative to a merger of Deutsche Bank/Commerzbank - Volker Brühl; Jan Pieter Krahnen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
In this exploratory article, we consider the future of Deutsche Bank and Commerzbank and develop a new approach to the topic: instead of a merger of DB and CB we propose to consider a partial merger of the IT and related back office functions in order to create the basis for an Open Banking platform in Germany. Such a platform would act as a cross-institutional infrastructure company in which the participating banks develop a common data and IT platform (while respecting the data protection regulations). Significant parts of the transaction processes would be pooled by the institutions and executed by the Open Banking platform. Moreover, the institutions remain legally independent and compete with each other at the level of products and services that are developed and produced using just this common data and IT platform - "national champions" would not be created. But such an "Open Banking Platform" could become even the nucleus of a European Banking platform that could be competitive with existing global data platforms from the USA and China which are already offering financial services and are likely to expand their offerings in the foreseeable future. The proposed model of an open data platform for banks prevents the emergence of national champions and supports the main goal of the banking union: creation of a financial system, in which single banks can be resolved without provoking a systemic crisis and forcing taxpayers to finance bailouts.
urn:nbn:de:hebis:30:3-503827
Keywords: 330; Open Banking Platform Germany; Banking Union; Merger; Deutsche Bank; Commerzbank